Effects of R & D implementation on the performance of publicly funded research in sultan qaboos university - Al Hosni, Fahad (Cranfield University, 2010)
Models of R&D account for technical, technological and administrative factors of R&D implementation but underestimate the influence of behavioural and political factors such as power and conflict. They assume that R&D organisation is “well-insulated” from partisan, emotions, political reactions and contextual factors and that decision makers are rational and decisions are taken to best fit the content of R&D programme. The present study explores the effects of rational and irrational factors in the R&D implementation process on the performance of publicly funded research projects in universities. It uses realist and qualitative exploratory semi-structured interviews with 22 active researchers in Sultan Qaboos University provides “depth and detail” of the complexities of R&D implementation effects on its performance. The study discovers 18 measures of success of academic research and 30 effects of R&D implementation of the performance of publicly funded research.The study concludes that the iterative, non-linear and processual nature of R&D implementation is a continuous dynamic system. R&D success builds up the capacity for future success whilst failures decrease the chances of future successes. The integrated effects of implementation (IEI) influence R&D performance through technical and administrative capability of the R&D organisation as well as through behaviours of organisation members. These include leaders’ behaviours, conflict and political skills within individuals. Both success dynamism and IEI suggest contextualism implementation of R&D.
Keywords: R&D success; performance measurement; university research; leadership; organisational behaviour; Higher Education